Formation, properties and role of residual waves as seeds in multiwavelength Brillouin-erbium fiber laser - Cholan, Noran Azizan; Al-Mansoori, Mohammed Hayder; Muhammad Noor, Ahmad Shukri; Ismail, Alyani; Mahdi, Mohd Adzir (Elsevier, 2014)
The formation, properties and role of residual waves of a multiwavelength Brillouin-erbium fiber laser (BEFL) which are responsible for the enhancement of the number of spectral lines in the BEFL are discussed and explored. The formation process which involves interplay of stimulated Brillouin scattering, Rayleigh scattering and four-wave mixing (FWM) in a highly nonlinear fiber is explained in this work. The properties of the residual waves (forward propagation) in terms of output spectra, output power and optical signal to noise ratio are compared with the waves of the BEFL (backward propagation) for better understanding. We find experimentally that the residual waves span over a wide band due to the mechanism of FWM and this is believed to play a key role in generating seeds for lasers in the BEFL. The present analysis of the formation, properties and role of the residual waves can well explain how the residual waves enhance the number of spectral lines and this understanding could be useful in creating quality seeds for the BEFL.